Habits in healthy nutrition, obesity, alcohol, smoking, among students of the Faculty of Physical Activity and Recreation - Çitozi, Robert; Bozo, Spartak; Spahiu, Elton (Arena-Journal of Physical Activities, 2017)
Albania is a country of Eastern Europe with a relatively young and predomi- nantly rural population. After the end of the communist regime in 1991, Al- bania experienced a difficult economic transition and suffered two economic shocks due to the financial collapse of the so-called â€œpyramid schemesâ€ in 1997 and to the Kosovo crisis in 1999. Since the 1990s, the supply of many food groups has increased, particularly for dairy products and eggs, and fruit and vegetables. Consequently the diet has become more diversified, espe- cially in urban areas. Presently, at national level, the dietary energy supply is largely sufficient to meet the populationâ€™s energy requirements. As a con- sequence, the dietary habits of young adults have been affected; thus, over- weight and obesity are increasingly being observed among the young. The purpose of this study is to assess the prevalence of overweight and obesity on a sample of students from the Â Sports University of Tirana and to exam- ine their eating habits. Methods. A cross-sectional survey of 150 students (63.3% male and 36.6% female), aged 18.69 years, were chosen randomly from the Sports University of Tirana (SUT) during October 2016. Students were asked to fill out a self-reported questionnaire that included questionsÂ on their eating, drinking and smoking habits. Also, their weight, height, and body mass index were measured. Body mass index (BMI) was used to assess studentsâ€™ weight status. Results. This study showed that the majority of the students (75.52 %) were of normal weight (69.36 % male students compared to 81.16 % female students). The prevalence of overweight and obesity was not common among male students compared to females (24.98 % and 11.96 % vs. 3.86 % and 1.98 %, respectively). In contrast, 4.9% female students were underweight as compared to 1.8% males. Eating habits of the students showed that the majority (70%) reported taking meals regularly. Healthier eating habits of female compared to male students in terms of daily break- fast intake are the same. 38.23% of female students reported eating breakfast daily compared to 45.65% of male students. Intake of colored vegetables and fruits was common among students. A total of 32.5% reported daily intake of colored vegetables with a small gender differences (32.35% females vs. 32.6% males). Alcohol intake to male students in terms of 2or 3 times per week was 2.17% and rarely 56.52%, while to females students was 2.94% and rarely 35.29%. Males at least 1 packet is 23.91% and rarely 15.21% , females at least 1 packet is 11.76% and rarely 5.88%. 70% of our students are never smoker. Conclusion. In spite of the overall low prevalence of over- weight and obesity in the studied sample, results indicate that university of sport students would possibly benefit from a nutrition and health promotion program to reduce the tendency of overweight and obesity, especially among male students, and to improve studentsâ€™ eating habits.